Prevalence and Factors Associated with Back Pain among Patients Undergoing Spinal Anesthesia at the University of Gondar Comprehensive and Specialized Hospital, North West Ethiopia: An Institutional Based Cross-Sectional Study. (27th January 2021) - Zeleke, Tadael Gudayu; Mersha, Abraham Tarekegn; Endalew, Nigussie Simeneh; Ferede, Yonas Admasu
Abstract : Background . Back pain is often reported as a common complaint after surgery. Many studies showed that the prevalence of back pain after spinal anesthesia is high and its magnitude is considerable in developing countries. It is highly related to reduced quality of life, loss of work productivity, burden of health care costs, and satisfaction regarding health care service; therefore, measures should be taken to reduce or prevented postspinal back. The aim of this cross-sectional study was to assess the prevalence and factors associated with back pain among patients undergoing spinal anesthesia at the University of Gondar Comprehensive and Specialized Hospital, Northwest Ethiopia. Methodology . An institutional based cross-sectional study was conducted from March to May 2020. A total of 215 participants were enrolled in this study. A convenience sampling technique was used to get the study participants. Both univariable and multivariable logistic regression were used to identify factors associated with postspinal back pain. Variables with a p value less than <0.2 in the bivariable analysis were fitted into the multivariable analysis. In the multivariable analysis, a variable with a p value of <0.05 was considered statistically significant. Results . The overall prevalence of postspinal back pain was 40.5% (95% CI: 34.0, 47.4). Being overweight (AOR = 3.8; 95% CI: 1.47, 9.96) and obese (AOR = 4.9; 95% CI: 1.19, 20.4), using big spinal needles (AOR = 5.9; 95% CI: 1.04, 33.4), two attempts of lumbar puncture (AOR = 5.5; 95% CI: 1.74, 17.59), more than three attempts of lumbar puncture (AOR = 4.9; 95% CI: 1.63, 15.2), and the number of bone contacts during spinal anesthesia procedure (AOR = 3.1; 95% CI: 1.14, 8.45) were positively associated with postspinal back pain. Conclusion and Recommendation . The overall incidence of back pain is high. Body mass index, size of spinal needle, number of attempts, and number of bone contacts are significantly associated with the incidence of back pain following spinal anesthesia. Thus, it is better to minimize the number of lumbar puncture attempts and bone contacts during spinal anesthesia to reduce postspinal back pain. In addition, using smaller size spinal needle is a good choice.